The young and restless: Re-examining media portrayals of youth - Ying, Shee Siew (Institutional Knowledge at Singapore Management University, 2017)
From TV programmes, to newspapers, books and magazines, traditional media’s depictions of youth have tended to dwell on either sides of two extremes: hapless victims or violent perpetrators.